2016
DOI: 10.1159/000452760
|View full text |Cite
|
Sign up to set email alerts
|

Intrapancreatic Accessory Spleen: A Diagnosis Not to Forget!

Abstract: A 69-year-old male patient was incidentally diagnosed with a 5-mm lesion in the pancreatic tail by endoscopic ultrasound (EUS). After contrast-enhanced EUS and EUS-elastography, all imaging features were highly suggestive of a benign pancreatic solid lesion such as an intrapancreatic accessory spleen (IPAS) or a benign neuroendocrine tumor. Interposition of the splenic artery precluded EUS-guided fine-needle aspiration (FNA). When an asymptomatic pancreatic mass is detected, IPAS diagnosis should be considered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…4 Other studies have suggested the usage of contrast-enhanced EUS and EUS-elastography as a useful tool for diagnosis of IPAS. 5 Appearance of the lesion in this case was a very unusual presentation for anIPAS, given its association within a mucinous cyst. This is a rare diagnosis with less than 60 reported cases.…”
Section: Discussionmentioning
confidence: 65%
“…4 Other studies have suggested the usage of contrast-enhanced EUS and EUS-elastography as a useful tool for diagnosis of IPAS. 5 Appearance of the lesion in this case was a very unusual presentation for anIPAS, given its association within a mucinous cyst. This is a rare diagnosis with less than 60 reported cases.…”
Section: Discussionmentioning
confidence: 65%
“…Ectopic splenic tissue can arise either from autotransplation via trauma (“splenosis”) or from a failure of a portion of the spleen to fuse with the main splenic tissue during development (“accessory spleen [AS],” “splenule,“ or “splenunculus”). [123] The prevalence of AS ranges from 10%–30%,[24] with the most recent 2017 meta-analysis of over 22,000 patients reporting 14.5% prevalence of AS. [5] It can be found anywhere from the vicinity of its original location to ovaries and testes, the most common location being the splenic hilum (62.1%) followed by the pancreatic tail (5.5%).…”
Section: Introductionmentioning
confidence: 99%
“…[12567] The latter especially can present as a diagnostic dilemma, as it can look similar to other pancreatic pathologies on imaging, such as pancreatic adenocarcinoma and neuroendocrine tumors. Since AS is usually an incidental finding that requires no treatment,[24] it is important to distinguish intrapancreatic AS (IPAS) from other pancreatic neoplasms to avoid unnecessary interventions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Eighty percent of the reported IPAS cases have had the radiological diagnosis of PEN. 1,5,6 The typical cytological characteristic of AS is the presence of small lymphocytes representing the white pulpa. Mixed inflammatory cells admixed with the small lymphocytes, endothelial cells and histiocytes are the other components of AS.…”
mentioning
confidence: 99%